EMPOWERING FISH FARMERS AND PROCESSORS TO COPE WITH THE CHALLENGES OF COVID-19 PANDEMIC: THE ROLE OF NIGERIAN STORED PRODUCTS RESEARCH INSTITUTE (NSPRI) (Proceedings International Conference on Fisheries and Aquaculture, 2022)
COVID-19 pandemic has impacted the whole word in several dimensions leaving the fishing communities in the rural areas more vulnerable. A huge proportion of this fishing communities derive their income from the sale of fish that are caught and processed using local smoking equipment. The lockdown occasioned by the pandemic has really made life difficult for this people. In responding to these challenges, Nigerian Stored Products Research Institute (NSPRI), an agency of the federal government of Nigeria built fish processing facilities for fish farmers and processors in six (6) different locations spread across Niger and Kwara State. The processing centres were constructed as a facility where all the unit operations from receiving fresh fish to packaging of dried fish can be carried out under hygienic condition. The centres were equipped with NSPRI’s improved smoking kilns, handling and processing utensils, and packaging materials for the marketing of dried fish. Fish farmers and processors in the various locations were trained on proper handling, processing, packaging, and marketing of their products. This intervention has alleviated the sufferings of the concerned communities and brings about a turnaround in their social economic status. The initiative has also improved community engagement among the fish farmers which has increased their output. They can produce better quality product and sell them to buyers in neighbouring towns. This study demonstrated the key role of government in providing succour for rural communities especially in times of pandemic such as COVID-19 that the world is just recovering from.
Keywords: fish processing; drying; quality; empowerment